Dietary practice and nutritional status and the respective effect of pulses-based nutrition education among adolescent girls in Northwest Ethiopia: a cluster randomized controlled trial - Mekonnen, Fantahun Ayenew; Biks, Gashaw Andargie; Azale, Telake; Mengistu, Netsanet Worku (Frontiers in Nutrition, 2023)
Background: Thinness and stunting are the most severe public health problems among adolescent girls in Ethiopia. An inadequate intake of protein-source foods is the most critical cause, mainly due to the non-affordability of animal-origin foods. However, research to what extent improving pulses-based food consumption could contribute to decreasing the magnitude of protein-energy undernutrition is limited. Objective: This trial aimed to evaluate the effectiveness of pulses-based nutrition education in reducing the proportion of thinness among adolescent girls. Methods: A two-arm cluster randomized controlled trial was conducted among adolescent girls in Northwest Ethiopia from December 2021 to June 2022. A total of 602 adolescent girls from four schools were enrolled in the trial. Schools were assigned to intervention and control groups using stratified cluster randomization method. Pulses-based nutrition education was the intervention, whereas the usual dietary practice of adolescent girls was the comparator. The education was delivered over four weeks on a 45 to 60 minutes session per week basis. Thinness was the primary outcome of the trial, measured by anthropometry. An intention-to-treat analysis method was used. A log-binomial regression model was fitted to the data. Relative risk with the respective confidence interval and p-value was calculated. A p-value of < 0.05 was used to declare statistical significance. Stata 16 software was used for the analysis. Results: About 89.37% of the participants in the intervention group and 92.36% in the control group completed the trial. The pulses-based nutrition education intervention did not show a significant difference in reducing the proportion of thinness among participants in the intervention group compared to participants in the control group, even though a significant difference was observed in terms of the consumption of pulses-based food. Conclusion: The present trial was statistically non-significant in reducing thinness among adolescent girls. Similar studies that utilize objective methods of ascertaining pulses-based food consumption need to be conducted. Trial registration: The trial was registered in the Pan African Clinical Trials Registry (PACTR202111605102515) on 12 November 2021. https://pactr.samrc.ac.za/Search.aspx Keywords: Cluster randomized trial; Nutrition education; Adolescent girls; Adolescents; Pulses; Legumes; Thinness; Underweight